The importance of including babies during their first year of life in public health programs: evaluation of results of a clinical program for babies - Cançado-Figueiredo, Márcia; Das Dores-Guarienti, Cinthya Aline; Saldanha-Sampaio, Mircelei; Michel, Jorge Artur; Menna Ruiz-Diaz, Bianca Giovanna (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: given the importance of promoting oral health during the first years of life, and being conscious of the difficulties facing the profession to provide care to this age group, the University extension program of the Clinic for Babies offers the profession and the dental students quality education to provide adequate care to this age group. By means of a philosophy based on the principle of education-prevention and using alternative treatment methods for diseases already present, this program integrates education with the needs of the population, offering dental care to patients up to 36 months of age. The purpose was to evaluate the profile of the patients attending the clinic, as well as the efficacy of the treatment proposed by the Clinic for babies. Methods: a longitudinal study was carried out analyzing the following variables: plaque control, quality of the diet, and caries activity of the patients that were part of the program. Initially, 1009 children up to 36 months of age participated in the program and they were all treated during year 2003. A follow up was carried out in 2005 and 827 children were examined which meant a loss of 19.04% of the sample. Results: by means of a Chi square test a significant improvement in plaque control was observed (21.27% - p ≤ 0.05), with a non cariogenic diet (33.96% - p ≤ 0.05), and with a decrease in the number of patients with active caries lesions (33.96% - p ≤ 0.05). Conclusions: with an efficient protocol of promotion of oral health, a statistical significant improvement was obtained for all the variables studied. It was noteworthy the preparation of the dentists to treat patients of this age group, where intervention on the factors that influence the most common oral diseases can be done, reducing the occurrence of these diseases and improving the oral health of the patients.